Factors affecting consumer buying behaviour of solar water pumping system. Issue 4 (2nd September 2019) - Kumar, Vikas; Hundal, Bikramjit Singh; Kaur, Kulwinder
Abstract : Purpose: The purpose of this paper is to identify the factors influencing farmers' intention to purchase solar water pumping systems (SWPS). Design/methodology/approach: The research is based on primary data that have been collected from a total of 345 solar pump users from different villages and rural areas of Punjab (India). Exploratory and confirmatory factor analysis and multiple regression analysis have been used to examine the collected data. Multiple regression analysis is used to examine the identified dimensions' impact on customer buying behaviour. Findings: The results of analysis validated that consumer buying behaviour is significantly determined by cost, performance and government initiatives dimensions. However, dimensions such as eco-friendly product, information regarding product and company, environmental concern and social influence were found insignificant. Research limitations/implications: The sample size has been selected on the basis of convenience sampling and sample has been taken from the rural area. Therefore, the result may not be representative of the overall population. The perception of respondents from one part may vary from another part of India. Originality/value: By providing an insight into factors affecting consumer buying behaviour of SWPS, the proposed research attempts to fill the gaps in literature by conducting an empirical study on consumer buying behaviour. As the study relates to SWPS users, findings will be of additional value to solar product companies and the government.